Librarian in the Knowledge Era - Soundara Rajan, V. (Journal of Information and Knowledge, 2000)
This paper is in four parts. Part 1 has a brief overview of Knowledge management. Its impact on libraries is described in Part 2. The constraints inherent in the technical information scene are mentioned in Part 3. Part 4 deals with the enhanced role, namely, adding value to information, in store for the librarians in the wake of Knowledge Management.